Oligo-Miocene mafic intrusions of the San Juan Volcanic Field, southwestern Colorado, and their relationship to voluminous, caldera-forming magmas - Lake, Ethan T.; Farmer, G. Lang (Geochimica et cosmochimica acta, 2015)
The trigger(s) of ignimbrite flare-ups in continental environments and their connection to “high power” mantle-melting events are the subject of ongoing debate, often hampered by the relative scarcity of mantle-derived basalts compared to voluminous amounts of intermediate and silicic lavas, intrusions, and welded-tuffs. This study focused on locating and analyzing mafic magmas in the San Juan Mountains of Colorado, the largest erosional remnant of the Oligocene Southern Rocky Mountain ignimbrite flare-up. The “flare-up in” the San Juan Volcanic Field (SJVF) has several potential explanations including: crustal anatexis or MASH processes from either an asthenospheric “high power” melting event triggered by rifting and/or lithospheric delamination or a lithospheric mantle “high power” event caused by exposure of Farallon metasomatism to the underlying asthenosphere. The required volumes of crustal melt (a column 34–45km tall over an area of 10,000km2) and crustal heterogeneity disqualify anatexis as a source of the SJVF. Basalt and basaltic andesite magmas of the SJVF have εNd (−6 to −8) and 87Sr/86Sr (0.705–0.706), high Ba concentrations (750–1500ppm) with low Rb/Zr (0.25–0.5) compatible with a lithospheric basalt MASH model. An OIB-like basalt source would require nearly twice the crustal assimilation (50%+) and MASH zone thickness (∼17km) to produce the isotopic ratios of intermediate to silicic SJVF rocks and could not produce their elevated Ba concentrations. The location of the SJVF may be controlled by its maximum distance of magma capture and lateral transport or by the underlying lithospheric mantle.